Virtual integration as an approach to engender product innovation and accelerate product development time: A literature analysis - Dadriyansyah, G.; Ibrahim, A.; Hassan, M.G. (IEEE Computer Society, 2011)
Global competitiveness has forced manufacturing firm, as an internal constituents, to work closer with their suppliers and customers in order to produce highly innovative product in shorter time interval. However as the business trends in manufacturing industry have evolved, centralized integration has become obsolete and no longer be eficient.Concurrent engineering methodology allows manufacturing firms to adopt a new collaboration approach called virtual integration. With the aid of computer-mediated communication, virtual integration is believed to be a promising solution to NPD collaboration issues. Therefore, this conceptual paper is aimed to seek for a new approach to engender product innovation which at the same time accelerates product development time in geographical dispersed setting through literature analysis. Some prepositions are developed to provide a preliminary understanding on this issue that would be beneficial for future research in this field.